The Art of Digital Marketing (International Journal of Scientific Research in Science and Technology, 2024)
The digital revolution has fundamentally reshaped the business landscape, particularly in marketing. This article explores the rise of "cyber consumers" and their evolving needs, along with the increasing significance of cyber business-to-business interactions. It emphasizes the need for innovative marketing strategies to cater to these transformed dynamics.